Life-cycle costs of a resource-oriented sanitation system and implications for advancing a circular economy approach to sanitation - Carrard, N.; Jayathilake, Nilanthi; Willetts, J. (Elsevier, 2021)
Implementing a circular economy approach to sanitation requires knowledge of the costs to construct, operate and maintain resource-oriented systems. Yet the dearth of data on costs of urban sanitation in general, and resource-oriented systems in particular, limit opportunities to progress sustainable sanitation in low- and middle-income countries. This paper contributes empirical data on the life-cycle costs of a resource-oriented sanitation system in urban Sri Lanka, addressing a gap in evidence about how much it costs, and who pays, for a system that integrates fecal sludge management with nutrient capture and reuse. Costs across the system life-cycle were analyzed according to: (i) cost type; (ii) phases of the sanitation chain; and (iii) distribution between actors. Over a 25-year lifespan, the system had an annualized cost of USD 2.8/person or USD 11/m3 of septage treated. Revenue from co-compost sales covered reuse-related costs plus 8% of present value costs for other phases of the sanitation chain. Findings affirm both the potential for resource-oriented sanitation to generate revenue, and the need for substantial complementary investment in the overall system. The system was found to be reliant on household investment, yet financially viable from the service provider perspective with revenue from desludging services (89%) and co-compost sales (11%) that exceeded costs over the system lifespan and in most years. The analysis of total costs, financial perspectives, and reuse specifics contributes critical evidence to inform policy and planning that supports a purposeful and equitable transition towards circular economy approaches to sanitation.